Tell el-Kheleifeh 1937-1940: A Reappraisal of Nelson Glueck's Excavations with Special Attention to the Site's Architectural and Ceramic Traditions - Pratico, Gary Davis
Th. D. diss.; Order No. DA8403846; "Assyrian" pottery; - Cf. DissAbstr 44/11 (1984) 3456-A.